The optimal method for improving postural balance in healthy young and older people: specific training for postural tasks encountered in personal physical practice - Paillard, Thierry (Frontiers in Physiology, 2023)
It is well known that regular exercise or physical activity (training) improves postural balance in healthy young and older subjects, but the optimal exercise or physical activity (i.e., likely to induce the greatest postural improvements) and the context in which it is carried out remain to be explored and determined for each population. The most beneficial adaptations would depend, in particular, on gestural conditions (body position, movement and gesture practiced) and material conditions (nature of the ground surface, sports equipment used, type of environment - stable or changing). In fact, the global postural adaptations induced by training do not result from the transfer between different trained and untrained postural tasks, but are the sum of the adaptations related to each trained postural task in healthy young and older subjects. Based on current knowledge, optimal training programs should include the full range of postural tasks encountered in personal physical practice for each population. To date, the method of implementing progressive postural balance tasks with different degrees of difficulty and instability has been used as the effective method to improve postural balance, but it should not be considered as the reference method. Instead, it should be considered as a complementary method to the one based on specific postural tasks. An intervention strategy is proposed for young and older adults consisting of three different steps (general, oriented and specific/ecologic training). However, some parameters still need to be explored and possibly reconsidered in future studies to improve postural balance in an optimal way.